INOVASI PENDIDIKAN AKHLAQ BERBASIS MANAJEMEN QOLBU di MI SUNAN KALIJOGO WOLUTENGAH KECAMATAN KEREK KABUPATEN TUBAN - Ninik Hidayati; Sadik (PREMIERE : Journal of Islamic Elementary Education, 2019)
The occurrence of acts and acts of violence lately is a phenomenon that we often witness. In fact it almost always adorns mass media information. One of the causes and perhaps this is the most important cause is due to a moral or moral crisis. Moral crisis occurs because some people no longer want to heed the guidance of religion, which normatively teaches adherents to do good, abandoning immoral acts and evil. The heart is a great gift that is given to humans. With a human heart can recognize, communicate, and even love Robnya. Like a tower, the heart has many doors. Like a mirror, the heart is able to absorb and reflect every image that comes to it. Then the influence, the object will enter the heart, and imprint in it, through the means of birth, namely the five senses or through the means of the mind, namely fantasy, lust, anger, morals formed in a fitrawi. Imagine if everyone then tried to base all their activities on a clean heart. Truly there will be a terrible explosion in changes in a person. The conclusion is that the qolbu management-based moral education innovation is an idea or new method offered by the author to be used in implementing moral education. It is hoped that this new idea or method will be able to improve the quality of moral education which is felt to be declining today.